A Monolithic Integrated Dual-Wavelength DFB Laser With Equivalent Inverse-Gaussian Apodized Grating - Bocheng Yuan; Jianqin Shi; Wenxuan Qi; Lianyan Li; Jilin Zheng; Rulei Xiao; Yuechun Shi; Xiangfei Chen; Ning Xu; Yunshan Zhang (IEEE Photonics Journal, 2020)
A monolithic integrated dual-wavelength DFB laser with inverse-Gaussian apodized sampled Bragg grating (IGASBG) is proposed and investigated. The IGASBG in the DFB laser is achieved by varying the duty cycle of sampled Bragg grating. The frequency spacing between the two lasing modes can be designed from 38 GHz to 660 GHz which covers almost the entire millimeter-wave range and reaches terahertz. The results proposed in this paper have great reference value for fabricating dual-wavelength semiconductor lasers.